First person - Sukalp Muzumdar (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Sukalp Muzumdar is first author on 'Genetic activation of Nrf2 reduces cutaneous symptoms in a murine model of Netherton syndrome', published in DMM. Sukalp conducted the research described in this article while a PhD student in the lab of Prof. Dr Sabine Werner and PD Dr Matthias Schäfer at ETH Zurich, Zurich, Switzerland. He is now a postdoctoral fellow in the lab of Jesse Gillis at Cold Spring Harbor Laboratory, Cold Spring Harbor, NY, USA, investigating the mechanisms behind rare diseases and exploring avenues for novel treatments.